Nanodiamond resonators fabricated on 8″ Si substrates using adhesive wafer bonding. (8th May 2017) - Lebedev, V; Lisec, T; Yoshikawa, T; Reusch, M; Iankov, D; Giese, C; Žukauskaitė, A; Cimalla, V; Ambacher, O
Abstract: In this work, the adhesive wafer bonding of diamond thin films onto 8″ silicon substrates is reported. In order to characterize bonded nano-crystalline diamond layers, vibrometry and interferometry studies of micro-fabricated flexural beam and disk resonators were carried out. In particular, surface topology along with resonant frequencies, eigenmodes and mechanical quality factors were recorded and analyzed in order to obtain physical parameters of the transferred films. The vibration properties of the bonded resonators were compared to those fabricated directly on 3″ silicon substrates.